Automation of Load Electricity Operating System Using PLC (Programmable Logic Controller) - Hairul; Fatahul Arifin; Romi Wilza; Zakaria Zakaria; Kurniawan; Yusuf Dewantoro Herlambang (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
Jakabaring PLTS on-grid with a capacity of 2 MW operates from 6:00 am to 5:00 pm. At 5:00 pm the PLTS connection to the load will be disconnected and replaced with PLN. If the PLN is off due to damage or during maintenance, a generator that is operated manually will be used. Problems in the process of combining energy sources from Solar Panels to PLN require a power target of up to 10 Kva where if the power is fulfilled then the energy source from Photovoltaic (PV) will be connected to PLN and vice versa. Errors and speed in operation can be minimized by means of automation of the system operating the power supply to the load by using a PLC (Programmable Logic Controller). Optimization as a step to optimize the electricity supply in the PLTS area makes it the first source of power generation that is connected to the load, the second order is PLN if the PLTS has no power output or there is a problem and the third order is generators if PLN and PLTS have no power output. For this reason, a tool is needed that functions to move the power source alternately using a PLC (Programmable Logic Controller) as an ATS (Automatic Transfer Switch) process controller, where the tool will work automatically changing the power source if there is a disturbance that causes it to be unable to supply electricity to the user's load and also as a priority regulator of solar power sources as the main source of electricity to the load. When transferring loads from one source to another with 3 different power sources, it is faster and more effective to use an ATS (Automatic Transfer Switch) with a PLC controller compared to Manual or COS (Change Over Switch).